Genomic surveillance reveals early detection and transition of delta to omicron lineages of SARS-CoV-2 variants in wastewater treatment plants of Pune, India - Rajput, Vinay; Pramanik, Rinka; Malik, Vinita; Yadav, Rakeshkumar; Samson, Rachel; Kadam, Pradnya; Bhalerao, Unnati; Tupekar, Manisha; Deshpande, Dipti; Shah, Priyanki; Shashidhara, L. S.; Boargaonkar, Radhika; et al. (Environmental Science and Pollution Research, 2023)
The COVID-19 pandemic has emphasized the urgency for rapid public health surveillance methods to detect and monitor the transmission of infectious diseases. The wastewater-based epidemiology (WBE) has emerged as a promising tool for proactive analysis and quantification of infectious pathogens within a population before clinical cases emerge. In the present study, we aimed to assess the trend and dynamics of SARS-CoV-2 variants using a longitudinal approach. Our objective included early detection and monitoring of these variants to enhance our understanding of their prevalence and potential impact. To achieve our goals, we conducted real-time quantitative polymerase chain reaction (RT-qPCR) and Illumina sequencing on 442 wastewater (WW) samples collected from 10 sewage treatment plants (STPs) in Pune city, India, spanning from November 2021 to April 2022. Our comprehensive analysis identified 426 distinct lineages representing 17 highly transmissible variants of SARS-CoV-2. Notably, fragments of Omicron variant were detected in WW samples prior to its first clinical detection in Botswana. Furthermore, we observed highly contagious sub-lineages of the Omicron variant, including BA.1 (similar to 28%), BA.1.X (1.0-72%), BA.2 (1.0-18%), BA.2.X (1.0-97.4%) BA.2.12 (0.8-0.25%), BA.2.38 (0.8-1.0%), BA.2.75 (0.01-0.02%), BA.3 (0.09-6.3%), BA.4 (0.24-0.29%), and XBB (0.01-21.83%), with varying prevalence rates. Overall, the present study demonstrated the practicality of WBE in the early detection of SARS-CoV-2 variants, which could help track future outbreaks of SARS-CoV-2. Such approaches could be implicated in monitoring infectious agents before they appear in clinical cases.
Keywords: Bioinformatics pipeline; COVID-19; Early warning; India; Next-generation sequencing; Omicron; Public health; SARS-CoV-2; wastewater; Wastewater-based epidemiology

Histidinal-based potent antimalarial agents - Meena, Chhuttan L.; Hingamire, Tejashri; Gupta, Tanya; Deshmukh, Bhagyashree; Karmodiya, Krishanpal; Joshi, Rakesh; Shanmugam, Dhanasekaran; Sanjayan, Gangadhar J. (ChemMedChem, 2023)
Herein we report the synthesis and evaluation of peptide-histidinal conjugated drug scaffolds, which have the potential to target the hemoglobin-degrading proteases falcipain-2/3 from the human malaria parasite. Scaffolds with various substitutions were tested for antimalarial activity, and compounds 8 g, 8 h, and 15 exhibited EC50 values of similar to 0.018 mu M, similar to 0.069 mu M, and similar to 0.02 mu M, respectively. Structure-based docking studies on falcipain-2/3 proteases (PDB:2GHU and PDB:3BWK) revealed that compounds 8 g, 8 h, and 15 interact strongly with binding sites of falcipain-2/3 in a substrate-like manner. In silico ADME studies revealed that the molecules of interest showed no or minimal violations of drug-likeness parameters. Further, phenotypic assays revealed that compound 8 g and its biotinylated version inhibit hemoglobin degradation in the parasite food vacuole. The identification of falcipain-2/3 targeting potent inhibitors of the malaria parasite can serve as a starting point for the development of lead compounds as future antimalarial drug candidates.
Keywords: artemisinin; chloroquine; digestive vacuole; docking; falcipains; falciparum; P

Tale of two waves: Delineating diverse genomic and transmission landscapes driving the COVID-19 pandemic in Pune, India - Niveditha, Divya; Khan, Soumen; Khilari, Ajinkya; Nadkarni, Sanica; Bhalerao, Unnati; Kadam, Pradnya; Yadav, Ritu; Kanekar, Jugal B.; Shah, Nikita; Likhitkar, Bhagyashree; Sawant, Rutuja; Thakur, Shikha; et al. (Journal of Infection and Public Health, 2023)
Background: Modern response to pandemics, critical for effective public health measures, is shaped by the availability and integration of diverse epidemiological outbreak data. Tracking variants of concern (VOC) is integral to understanding the evolution of SARS-CoV-2 in space and time, both at the local level and global context. This potentially generates actionable information when integrated with epidemiological outbreak data.Methods: A city-wide network of researchers, clinicians, and pathology diagnostic laboratories was formed for genome surveillance of COVID-19 in Pune, India. The genomic landscapes of 10,496 sequenced samples of SARS-CoV-2 driving peaks of infection in Pune between December-2020 to March-2022, were determined. As a modern response to the pandemic, a ``band of five'' outbreak data analytics approach was used. This integrated the genomic data (Band 1) of the virus through molecular phylogenetics with key outbreak data including sample collection dates and case numbers (Band 2), demographics like age and gender (Band 3-4), and geospatial mapping (Band 5).Results: The transmission dynamics of VOCs in 10,496 sequenced samples identified B.1.617.2 (Delta) and BA(x) (Omicron formerly known as B.1.1.529) variants as drivers of the second and third peaks of infection in Pune. Spike Protein mutational profiling during pre and post-Omicron VOCs indicated differential rank ordering of high-frequency mutations in specific domains that increased the charge and binding properties of the protein. Time-resolved phylogenetic analysis of Omicron sub-lineages identified a highly divergent BA.1 from Pune in addition to recombinant X lineages, XZ, XQ, and XM. Conclusions: The band of five outbreak data analytics approach, which integrates five different types of data, highlights the importance of a strong surveillance system with high-quality meta-data for understanding the spatiotemporal evolution of the SARS-CoV-2 genome in Pune. These findings have important implica-tions for pandemic preparedness and could be critical tools for understanding and responding to future outbreaks.& COPY; 2023 Published by Elsevier Ltd on behalf of King Saud Bin Abdulaziz University for Health Sciences. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: COVID-19; Delta; Omicron; SARS-CoV-2 genomic surveillance; Variant of concern; Whole Genome Sequencing (WGS)

32nd National Congress of Parasitology, Pune: bringing together India's parasitologists - Purkayastha, Devatrisha; Pandit, Kushankur; Upadrasta, Sindhuri; Khilari, Ajinkya; Shanmugam, Dhanasekaran; Karmodiya, Krishanpal (Trends in Parasitology, 2025)
The 32nd National Congress of Parasitology (NCP) was held in person, 3-5 October 2024, at the Indian Institute of Science Education and Research Pune (IISER Pune), jointly organized by IISER Pune; the Council of Scientific and Industrial Research - National Chemical Laboratory, Pune; and Savitribai Phule Pune University (formerly University of Pune) in association with the Indian Society for Parasitology. The conference brought together around 250 attendees from across the country and abroad, including a diverse group of researchers, clinicians, industry experts, and students. The event provided a collaborative environment for exchanging research ideas relevant to the field of parasitology. The congress emphasized the concept of One Health, a holistic approach to address parasitic infections affecting humans and animals to promote overall health and well-being. In this TrendsTalk, the organizers provide an overview of the conference proceedings, which brought together India's vast and diverse parasitology community.

Long-term genomic surveillance of SARS-CoV-2 in campus wastewater depicts lineage trends and public health implications during and after omicron waves - Pramanik, Rinka; Rajput, Vinay; Malik, Vinita; Nannaware, Kiran; Matra, Sejal; Joshi, Sai; Kumar, Shubham; Samson, Rachel; Yadav, Rakesh Kumar; Shah, Priyanki; Shashidhara, LS; Dastager, Syed; et al. (Environment & Health, 2025)
SARS-CoV-2 transmission and detection on academic campuses in low- to middle-income countries has not been explored. The present study explored wastewater surveillance of SARS-CoV-2 in a campus setting in Pune, Maharashtra, India, offering insights into variant-specific trends and their correlation with clinical cases over a 2.5 year period from November 2021 to April 2024. We collected 242 wastewater samples from the campus sewershed and processed them to extract RNA and perform RT-qPCR and sequencing, followed by lineage assignment using the LCS tool. Early signals of different SARS-CoV-2 variants, such as BA.2.X, JN.1.X, and KP.2.X, were detected in wastewater prior to its first clinical report in Maharashtra, India. Wastewater viral load strongly correlated with clinical cases during the Omicron phase (ρ = 0.73–0.81) compared to the post-Omicron phase (ρ = −0.06 to 0.31). This study also highlights that alerts and warnings issued on the basis of wastewater viral hikes have proven instrumental in preventing outbreaks of SARS-CoV-2 variants on campus. However, downgrading COVID-19 from pandemic status by the WHO resulted in a subsequent decrease in public vigilance, changing the viral dynamic in the last phase of the study. This study showcases the utility of wastewater surveillance in a campus setting as an early warning system and understands the interplay of public health policy effects in viral dynamics within controlled ecosystems, such as campuses or offices.